Antimicrobial Activity of Crude Fractions of Gossypium barbadense Leaves and Isolation of Stigmasterol - Saddiq, Maryam; Salisu, Ahmed; Kabir, Kamaluddeen; Hassan, Yusuf (Pharmaceutical Sciences and Research, 2023)
Plants have been used in traditional medicine in different parts of the world to treat several diseases. Many studies have confirmed their medicinal values, which have led to the isolation and characterization of various potential drug candidates. This study focuses on the antimicrobial activity of crude fractions of Gossypium barbadense leaves and the isolation of active compound. The pulverized plant leave was soaked in ethanol (98% v/v), and a solvent-based fractionation was carried out using n-hexane, chloroform, ethyl acetate, and ethanol. The obtained crude fractions were screened for antimicrobial activity against four (4) clinical isolates: Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Candida albicans. NMR and FTIR analyses of the most active fraction were carried out. The ethanol fraction showed the highest extraction yield and premier antimicrobial activity against the tested organisms. At 500 mg/mL, the fraction showed inhibition of 28.50±1.14, 26.40±1.46, 21.00±0.05 and 18.03±0.41 mm against E. coli, P. aeruginosa, S. aureus, and C. albicans respectively. The lower Minimum Inhibitory Concentration (MIC) values of 12.5 mg/mL were obtained against E. coli and P. aeruginosa. NMR and FTIR analyses revealed that the isolated compound is stigmasterol, which is known to possess antimicrobial properties. However, compounds that were not isolated could have also contributed significantly to the antimicrobial activities of the fraction. Results of this study justifies the use of leaves extract of Gossypium barbadense as an antimicrobial agent.